Introduction to the sciences of hadith - Abdullah, Ismail; Abdul Manas, Shayuthy (IIUM Press, 2009)
The accurate understanding of hadith and its related Sciences is indispensable as to comprehend the true understanding of the Qur'an and the Islamic teachings respectively.